Effect of organic loading rate on anaerobic digestion performance of mesophilic (UASB) reactor using cattle slaughterhouse wastewater as substrate - Musa, Mohammed Ali; Idrus, Syazwani; Che Man, Hasfalina; Nik Daud, Nik Norsyahariati (MDPI, 2018)
In this study, the performance of a laboratory scale upflow anaerobic sludge blanket (UASB) reactor operating at mesophilic temperature (35 °C) was examined. Cattle slaughterhouse wastewater (CSWW) was used as the main substrate. The total and effective volumes of the reactor were 8 L and 6 L, respectively. Twelve different organic loading rates (OLR) were applied and the performance was evaluated. The chemical oxygen demand (COD) removal efficiency was more than 90% during batch study. In the continuous study, COD removal was also approximately 90% at OLR 0.4 g/L d-1 which subsequently dropped to below 50% when the loading rate increased to 15 g/L d-1. Approximately 5 L/d of biogas was obtained with high methane concentration at stages VI and XI corresponding to OLR of 2 and 10 g/L d-1, respectively. It was observed that the concentration of volatile fatty acids was low and that the alkalinity of the wastewater was sufficient to avoid acidification. Specific methane yields of 0.36 and 0.38 LCH₄/g COD added were achieved at OLR 7 and 10 g/L d-1. A hydraulic retention time (HRT) of 1 day was sufficient to remove greater than 70% of COD which correspond to 89% methane concentration. Parameters like soluble COD, NH₃-N, pH, alkalinity, total suspended solid (TSS), fats, oil, and grease were also investigated. The results show that the UASB reactor could serve as a good alternative for anaerobic treatment of CSWW and methane production.